İSTENMEYEN ÖĞRETMEN DAVRANIŞI ÖLÇME ARACI GELİŞTİRİLMESİ - Ömer BEYHAN (Fırat University, 2019)
Undesirable behaviors are those actions which are inappropriate for the situation or context in question, but they are consciously developed. In this context, all of the behaviors that hinder educational activities in the class and at school can be considered as undesirable/negative behaviors (Sağlam, 2007). However, when undesirable behaviors at schools are mentioned, inappropriate student behaviors come to the mind first. In fact, teachers may also exhibit some undesirable behaviors, and these behaviors negatively affect the learning process and learners' behaviors (Bonfield, 2003; Dolin, 1995; Toale 2001) or such behaviors might destroy learners' self-esteem and learning abilities (Çıngır, 2004). This study aims to test validity and reliability of "the scale for aggressive teacher behavior in the classroom based on learner perceptions," which was developed to reveal teacher aggression that educational faculty students have encountered so far during their educational life, and it also aims to examine the accuracy of the model that emerged as a result of the analyses. The aggressive teacher behavior scale with totally 38 items was administered to 357 university students and through exploratory factor analysis it was found that the scale had two factors. The values obtained through the exploratory and confirmatory factor analyses imply that the scale is valid, reliable and has a strong theoretical background.